REPRESENTASI JEJAK MEMORI BUDAYA LOKAL DALAM KARYA PERFORMANCE ART SENIMAN INDONESIA - Puri, Litya Ainunning; Handriyotopo, Handriyotopo; Qonita, Khoirunnisa (UI Scholars Hub, 2023)
This article offers an interpretation of performance artworks that serve as representations of local identity and values in the period of Indonesian new media artists. By emphasizing on local identity, this article seeks to reveal how artists respond to global challenges through artworks while capturing the aesthetics and values prevailing throughout Nusantara (the Indonesian archipelago). Additionally, this research offers an analysis of the timeline and geographic distribution of performers from the standpoint of the growth of new media art. Data were collected using a variety of methods, including observation, interview, and literature review involving both historical archives and literary works. Findings indicate that the two periods of performance art history, i.e. the early era and the digital age, are historically and geographically separated. Even if globalization has affected arts, local identity has never really disappeared during this time; in fact, it is growing stronger. Representations of the archipelago is a sign of the new emerging artists’ presence in the contemporary international art scene. The influence of local identity in artworks, however, is no longer debatable and can reflect an artist's self-identification.